Analytical investigation on the geometry of longitudinal continuous track in high-speed rail corresponding to lateral bridge deformation. (25th January 2021) - Lai, Zhipeng; Jiang, Lizhong; Liu, Xiang; Zhang, Yuntai; Zhou, Wangbao
Highlights: Lateral mapping rail deformation in HSR lines is established using the Ritz method. CRTSII track's continuity is considered in lateral mapping rail deformation. Extra connections in CRTSII track such as shear grooves are considered. Abstract: This study presents an analytical method to describe the geometry status of the track of a high-speed rail (HSR) line when the bridges are subjected to different types of lateral deformation. In this study, the longitudinal continuous ballast-less track, which is widely used in the HSR line, was adopted as the standard track laid on the bridge. By considering a sufficient length of the track extended beyond the bridge, the influences of the bridge deformation on the geometry changes of the track were evaluated. Based on the Ritz method, the energy functionals for the rail, slab, and base plate of tracks were established, and the expressions of the track deformations were analytically obtained. Considering the compatibility of deformation of each component of the track, the deformation of every track component was analytically solved. Moreover, a finite element (FE) model was established to validate the proposed analytical mapping model. The results obtained from both the FE model and the analytical mapping model were found to be in good agreement. Moreover, the contributions of the material parameters of the track components to the track geometry were further evaluated and discussed. The results indicated that the longitudinal continuous ballast-less track exhibited significant effects on the mapping relationship between the deformations of the track and the bridges. The shear grooves contributed significantly to the mapping rail deformation. The contributions of the lateral blocks could not be neglected. The contributions of the stiffness of the cement asphalt layer and the sliding layer to the mapping rail deformation were also noticeable.